Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. XYZ Divisi 1 Bagian Pemanen - Putra, Eka (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
The purpose of this study is to determine the effect of occupational safety and health on the productivity of PT. XYZ Division 1 Harvest Division. To achieve these objectives a study was conducted using a sample of 42 people, using the census method. The data analysis method uses simple linear regression. Based on test results on occupational safety and health variables (X) obtained tcount (3.751) is greater than the value of table (2.021) with a significant level of 0.01 < 0.05. So it can be concluded that Ho was rejected and Ha was accepted, which means that occupational health and safety had a significant effect on the productivity of the employees of PT. XYZ Division 1 Harvest Division. Based on the results of calculations to see how much the percentage of the contribution of the independent variable to the dependent variable, after processing the data it turns out that the value obtained (R2) = (0.510 X 0.510 = 0.260) or 26%, then the percentage of contribution or contribution of the independent variable to the dependent variable is 0.260 or 26 % while the remaining 74% is influenced by other variables that are ignored or not examined in this study. Recommendations that can be submitted are expected that occupational health and safety of employees must be tightened even more, such as prohibiting the deviation of dangerous goods because they received the lowest response of 3.31 on a statement of agreement, it can be said that occupational health and safety the main priority for employees is with employees